Cyanophage Propagation in the Freshwater Cyanobacterium Phormidium Is Constrained by Phosphorus Limitation and Enhanced by Elevated pCO2 - Cheng, Kai; Frenken, Thijs; Brussaard, Corina P. D.; Van de Waal, Dedmer B. (Frontiers in Microbiology, 2019)
Intensification of human activities has led to changes in the availabilities of CO2 and nutrients in freshwater ecosystems, which may greatly alter the physiological status of phytoplankton. Viruses require hosts for their reproduction and shifts in phytoplankton host physiology through global environmental change may thus affect viral infections as well. Various studies have investigated the impacts of single environmental factors on phytoplankton virus propagation, yet little is known about the impacts of multiple factors, particularly in freshwater systems. We therefore tested the combined effects of phosphorus limitation and elevated pCO2 on the propagation of a cyanophage infecting a freshwater cyanobacterium. To this end, we cultured Phormidium in P-limited chemostats under ambient (400 μatm) and elevated (800 μatm) pCO2 at growth rates of 0.6, 0.3, and 0.05 d-1. Host C:P ratios generally increased with strengthened P-limitation and with elevated pCO2. Upon host steady state conditions, virus growth characteristics were obtained in separate infection assays where hosts were infected by the double-stranded DNA cyanophage PP. Severe P-limitation (host growth 0.05 d-1) led to a 85% decrease in cyanophage production rate and a 73% decrease in burst size compared to the 0.6 d-1 grown P-limited cultures. Elevated pCO2 induced a 96% increase in cyanophage production rate and a 57% increase in burst size, as well as an 85% shorter latent period as compared to ambient pCO2 at the different host growth rates. In addition, elevated pCO2 caused a decrease in the plaquing efficiency and an increase in the abortion percentage for the 0.05 d-1 P-limited treatment, while the plaquing efficiency increased for the 0.6 d-1 P-limited cultures. Together, our results demonstrate interactive effects of elevated pCO2 and P-limitation on cyanophage propagation, and show that viral propagation is generally constrained by P-limitation but enhanced with elevated pCO2. Our findings indicate that global change will likely have a severe impact on virus growth characteristics and thereby on the control of cyanobacterial hosts in freshwater ecosystems.